PENINGKATAN KAMPUNG SAYUR ORGANIK DAN AKUAPONIK MELALUI PELATIHAN PEMBUATAN AKUAPONIK DARI BAHAN BEKAS - Jatmiko, Andriyan Rizki; Pamuji, Fandi Yulian; Gabriella, Widea (LPPM Universitas Al Muslim, 2024)
Rapid development has an impact on urban land which keeps decreasing, thus, the use of narrow yards is a solution to support urban farming. One effective method of urban farming is the aquaponics technique, in which plants and fish are grown together in the same container. The problems overcome through this approach are: 1) limited urban land means limited use of yards, and 2) not all residents have the knowledge and skills to implement aquaponic cultivation appropriately. Therefore, there is a need for a training on how to create and cultivate aquaponics efficiently. This community service activity aimed to increase productivity, economic independence and nutritional fulfillment through the practice of urban farming with aquaponics in Bandulan Village RT 05 RW 08, in the form of outreach, assistance and comprehensive training for residents who need it. The results of this activity are a pilot aquaponics system managed by Karang Taruna, increasing community knowledge, and motivation to implement an aquaponics system around the house as an alternative to meet vegetable and fish needs. Apart from that, it contributes in supporting sustainable urban agriculture in Bandulan Village.